2007
DOI: 10.1371/journal.pone.0000792
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Morphology in Capuchin Monkeys Is Influenced by Sex and Handedness

Abstract: Sex differences have been reported in both overall corpus callosum area and its regional subdivisions in humans. Some have suggested this reflects a unique adaptation in humans, as similar sex differences in corpus callosum morphology have not been reported in any other species of primate examined to date. Furthermore, an association between various measurements of corpus callosum morphology and handedness has been found in humans and chimpanzees. In the current study, we report measurements of corpus callosum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
3
33
1
Order By: Relevance
“…Previous research has found significant sex differences in male and female capuchins [Phillips et al, 2007], with males having smaller CC:brain ratios than females and smaller splenia than females. These sex differences were also found in our sample.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous research has found significant sex differences in male and female capuchins [Phillips et al, 2007], with males having smaller CC:brain ratios than females and smaller splenia than females. These sex differences were also found in our sample.…”
Section: Discussionmentioning
confidence: 90%
“…CC area measurements were taken from the midsagittal slice using a method similar to that described by Sanchez et al [1998] and others [Phillips et al, 2007[Phillips et al, , 2009Pierre et al, 2008] in non-human primates. The method divides the CC into five segments which are roughly associated with different sets of fiber projections to various cortical regions of the brain [Pandya et al, 1971;Witelson, 1989] (Fig.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hellner-Burris et al (2010) suggested a relationship among prey capture, the degree of lateralization and the morphology of the corpus callosum in capuchin monkeys, and our findings suggest that this set of related asymmetries may have an adaptive explanation. However, the neurobiological bases of hand preference remain unresolved (Phillips & Hopkins, 2007), even though manual laterality in capuchins and chimpanzees seem to be linked to brain asymmetries (Dunham & Hopkins, 2006;Hopkins & Cantalupo, 2004;Hopkins, Cantalupo, & Taglialatela, 2007;Phillips & Hopkins, 2007;Phillips & Sherwood, 2005;Phillips, Sherwood, & Lilak, 2007).…”
Section: In Primatesmentioning
confidence: 99%
“…Capuchin monkeys are largebrained, socially complex primates with a rich vocal repertoire (Di Bitetti, 2003Gros-Louis, 2004;Jack, 2007;Rilling & Insel, 1999). Given these characteristics and recent findings of neuroanatomical asymmetries and their relationship to lateralised behaviour in capuchins (Phillips & Hopkins, 2007;Phillips & Sherwood, 2005;Phillips, Sherwood, & Lilak, 2007), it was hypothesised that they would display leftward asymmetry of the SF. While Hopkins et al (2000) reported leftward asymmetry in the medial region of New World monkeys, their sample only consisted of four capuchin monkeys and four squirrel monkeys (Saimiri sciureus), and analyses pooled both species.…”
mentioning
confidence: 99%